Global perspective of treatment failures - Herschorn, Sender (Canadian Urological Association Journal, 2013)
Overactive bladder (OAB) is a highly prevalent condition, affecting approximately 18% of adult Canadians. The impact of OAB is substantial, negatively affecting quality of life, sexuality and work productivity. Furthermore, patients with OAB are at increased risk of several other important comorbidities, including mood and anxiety disorders. Despite widespread availability of efficacious treatment, research has shown that OAB remains underdiagnosed and undertreated.